Trachoma prevention practice and associated factors among mothers having children aged under nine years in Andabet district, northwest Ethiopia, 2022: A multi-level analysis. - Zufan Alamrie Asmare; Natnael Lakachew Assefa; Dagmawi Abebe; Solomon Gedlu Nigatu; Yezinash Addis Alimaw (PLoS Neglected Tropical Diseases, 2023)
Background The world health organization (WHO) adopted the Surgery, Antibiotic, facial cleanliness, and environmental improvement (SAFE) strategy for the prevention of trachoma, and different prevention strategies have been employed in Andabet district. Trachoma still has a high prevalence despite these efforts. So, it is imperative to assess ground trachoma prevention practice (TPP) since there are insufficient studies in the study area. Objective To determine the magnitude and factors associated with TPP among mothers having children aged under nine years in Andabet district, Northwest Ethiopia. Method A community-based cross-sectional study involving 624 participants was conducted June 1-30, 2022. Systematic random sampling was carried out to select study participants. Multi-level binary logistic regression analysis was used to identify factors associated with poor TPP. Descriptive and summary statistics were performed and variables with p-value < 0.05 in the best-fitted model were declared to be significantly associated with poor TPP. Results In this study, the proportion of poor TPP was found to be 50.16% (95%CI = 46.23, 54.08). In the multi-variable multi-level logistic regression; having no formal education (AOR = 2.95; 95%CI: 1.41,6.15) and primary education (AOR = 2.33; 95%CI:1.04, 5.24), being a farmer (AOR = 3.02; 95%CI:1.73,5.28), and merchant (AOR = 2.63; 95%CI:1.20, 5.75), time taken to water point >30 minutes (AOR = 4.60,95CI:1.30,16.26) and didn't receive health education about trachoma (AOR = 2.36;95CI:1.16,4.79) were significantly associated with poor TPP. Conclusion The proportion of poor TPP was high relative to other studies. Level of education, occupation, time taken to the water point, and health education were significantly associated with poor TPP. Therefore, taking special attention to these high-risk groups could decrease the poor TPP.